Constructivism Methods In Procurement Arabic Speaking Ability for Early Children - Taufiq, Ahmad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The age of the child is the right age to teach foreign languages including Arabic, which is expected to be achieved optimally, but it is not easy to teach foreign languages for the age of the child, the basic abilities possessed when a child learns mother tongue, his brain is still clean and has not yet got the influence of other languages, due to cognitive and affective functions both.This Study uses qualitative research, with descriptive analysis, using literatus study, Cognitive as an initial theory that can support the back of the constructivism method lifts Piaget's cognitive theory and cognitive theory vygotsky, language acquisition in speaking ability is to imitate the information received by children, which in this case is early childhood, learning in cognitive development is included in Meaningful learning theory and the essence of this learning is that what children learn has a function for their lives, and constructivism further emphasizes the importance of learning to associate new experiences, phenomena and facts into the understanding system they have. The educational environment is a pillar for the ongoing practice of contextual daily life. In this environment communication practices are applied in accordance with learning patterns. Opportunities to interact, use the abilities that have been obtained in the lesson, understand the context of a sentence, and interpret the utterances as completeness in learningKeywords: Child, Cognitive, Piaget, Vygotsky, Communication